An Annotated Translation of the Mūlamadhyamakakārikā and discussion of pratītyasamutpāda in Prasannapadā into Thai (1) - พิทักษ์ธีระธรรม เมธี; มั่งมีสุขศิริ สมบัติ (Dhammadhara Journal of Buddhist Studies, 2018)
The present article is the first part of a Thai translation of the Mūlamadhyamakakārikā, based primarily on the Sanskrit version but also in conjuction with a careful comparison of the Tibetan and Chinese translations. In addition, there is a Thai translation of discussion of pratītyasamutpāda in Prasannapadā, commentary Mūlamadhyamakakārikā composed by Candrakīrti. Annotated footnotes are included to help readers understand the text.